2020
DOI: 10.21273/hortsci14542-19
|View full text |Cite
|
Sign up to set email alerts
|

Amending Sandy Soil with Biochar Promotes Plant Growth and Root Colonization by Mycorrhizal Fungi in Highbush Blueberry

Abstract: Biochar, a carbon-rich, fine-grained residue obtained from pyrolysis of biomass, is known to improve soil conditions and to suppress infection by soilborne pathogens. However, its use as a soil amendment has received relatively little attention by the horticulture industry. Two 12-week experiments were conducted in a greenhouse to determine the potential of using biochar, produced from mixed conifers during conversion of wood to energy, as a soil amendment for highbush blueberry (Vaccinium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
2
9
1
Order By: Relevance
“…Biochar is known to act as a liming agent (Trippe et al, 2015). However, we did not find this to be the case in this or our previous study with biochar for blueberry (Sales et al, 2020). In both cases, the biochar was produced from wood debris obtained from mixed conifer species.…”
Section: Strikcontrasting
confidence: 58%
See 2 more Smart Citations
“…Biochar is known to act as a liming agent (Trippe et al, 2015). However, we did not find this to be the case in this or our previous study with biochar for blueberry (Sales et al, 2020). In both cases, the biochar was produced from wood debris obtained from mixed conifer species.…”
Section: Strikcontrasting
confidence: 58%
“…To increase organic matter, growers often incorporate bark or sawdust into the soil before planting blueberry, as well as use them as mulch afterward; however, the cost of these materials is increasing and availability is limited in many regions (Larco et al, 2013a). Recently, we conducted greenhouse experiments to determine whether biochar could be used as an alternative amendment for highbush blueberry (Vaccinium hybrid) (Sales et al, 2020). The biochar in this case was produced from mixed conifers during conversion of wood to energy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural soils rarely meet these requirements. Thus, growers traditionally prepare fields with the addition of sulfur, organic matter, or other amendments [69][70][71]. Even with these inputs, SHB soil preferences limit the areas where it can be planted.…”
Section: Container-based Productionmentioning
confidence: 99%
“…Another study, where the authors evaluated the effect of eight biochar amendments on the severity of soybean root rot caused by Fusarium virguliforme in a silty clay loam, showed no evidence of systemic and indirect effects of biochar on severity of soybean root rot (Rogovska et al 2017). Sales et al (2020) also found no effect on the suppression of phytophthora root rot of highbush blueberry (Vaccinium hybrid 'Legacy') in a sandy soil amended with a commercial biochar manufactured from mixed conifers and inoculated with Phytophthora cinnamomic. The root infection by P. cinnamomi also increased with the increase biochar application rate and this effect could partly be explained by the organic compounds found in biochar.…”
Section: Biochar Effect On Plant-soil-microorganism Interactionsmentioning
confidence: 99%